2022
DOI: 10.1108/oir-08-2021-0448
|View full text |Cite
|
Sign up to set email alerts
|

The application of emotions, sharing motivations, and psychological distance in examining the intention to share COVID-19-related fake news

Abstract: PurposeCoronavirus disease 2019-related fake news consistently appears on social media. This study uses appraisal theory to analyze the impact of such rumors on individuals' emotions, motivations, and intentions to share fake news. Furthermore, the concept of psychological distance and construal level theory are used in combination with appraisal theory to compare toilet paper shortages and celebrity scandal rumors.Design/methodology/approachData collected from 299 Taiwanese respondents to 150 toilet paper sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Several studies have indicated that users who share systems with their families and friends are likely to continue using these systems. 86 , 87 However, in the present study, we determined that these effects are not direct; that is, users are locked in if they only experience mutual benefit.…”
Section: Discussionmentioning
confidence: 75%
“…Several studies have indicated that users who share systems with their families and friends are likely to continue using these systems. 86 , 87 However, in the present study, we determined that these effects are not direct; that is, users are locked in if they only experience mutual benefit.…”
Section: Discussionmentioning
confidence: 75%
“…Individual reactions to the same situation vary by gender (Etheridge & Spantig, 2020). There is evidence that the belief in fake news is moderated by a variety of factors, including knowledge (Apuke & Omar, 2020), emotion (Tan & Hsu, 2022), and media literacy (Chen et al, 2021). However, the influence of gender differences has not been discussed in previous studies.…”
Section: Gender As Moderatormentioning
confidence: 99%
“…Therefore, they assert that rather than assessing how specific emotions impact perceptions of fake news, we should evaluate how emotion in general affects belief in misinformation. Recently, Tan and Hsu (2022) examined how emotions triggered by reading false stories play a role in misinformation sharing. They showed that surprise and worry play a prominent role in driving altruistic sharing motivation after exposure to COVID-19-related misinformation about a toilet paper shortage.…”
Section: Literature Reviewmentioning
confidence: 99%